Substrate‐Independent Magnetic Bistability in Monolayers of the Single‐Molecule Magnet Dy2ScN@C80 on Metals and Insulators. (24th January 2020) - Krylov, Denis S.; Schimmel, Sebastian; Dubrovin, Vasilii; Liu, Fupin; Nguyen, T. T. Nhung; Spree, Lukas; Chen, Chia‐Hsiang; Velkos, Georgios; Bulbucan, Claudiu; Westerström, Rasmus; Studniarek, Michał; Dreiser, Jan; et al.
Abstract: Magnetic hysteresis is demonstrated for monolayers of the single‐molecule magnet (SMM) Dy2 ScN@C80 deposited on Au(111), Ag(100), and MgO|Ag(100) surfaces by vacuum sublimation. The topography and electronic structure of Dy2 ScN@C80 adsorbed on Au(111) were studied by STM. X‐ray magnetic CD studies show that the Dy2 ScN@C80 monolayers exhibit similarly broad magnetic hysteresis independent on the substrate used, but the orientation of the Dy2 ScN cluster depends strongly on the surface. DFT calculations show that the extent of the electronic interaction of the fullerene molecules with the surface is increasing dramatically from MgO to Au(111) and Ag(100). However, the charge redistribution at the fullerene‐surface interface is fully absorbed by the carbon cage, leaving the state of the endohedral cluster intact. This Faraday cage effect of the fullerene preserves the magnetic bistability of fullerene‐SMMs on conducting substrates and facilitates their application in molecular spintronics. Abstract : Monoschichten aus Dy2 ScN@C80 zeigen eine magnetische Hysterese auf Au‐, Ag‐ und MgO|Ag‐Substraten. Die Substrate beeinflussen die Anordnung des endohedralen Clusters, aber nicht die Breite der Hysterese. Der Kohlenstoffkäfig schützt den endohedralen Magnetcluster und sorgt so für die Aufrechterhaltung der magnetischen Bistabilität.